66.5k views
2 votes
The function h(x)=x^2+3 and g(x)=x^2-6. If g(x)=h(x)+k, what is the value of k?

1 Answer

1 vote

Answer:

-9

Explanation:

Since h(x) = x^2 + 3 and g(x) = x^2 -6, they only differ by about 9 units or 3 --6 = 9. This means a value was added /subtracted to h(x) to get g(x). This value is k.

So g(x) = h(x) - 9 where k = -9, since x^2 + 3 - 9 = x^2 -6.

User Stephen Hynes
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.